Direct Patterning of Organic Functional Polymers through Conventional Photolithography and Noninvasive Cross‐Link Agents. Issue 26 (6th May 2016) - Squillaci, Marco A.; Qiu, Feng; Aliprandi, Alessandro; Zhang, Fan; Feng, Xinliang; Samorì, Paolo
Abstract : A new technique for direct patterning of functional organic polymers using commercial photolithography setups with a minimal loss of the materials' performances is reported. This result is achieved through novel cross‐link agents made by boron‐ and fluorine‐containing heterocycles that can react between themselves upon UV‐ and white‐light exposure.